2012
DOI: 10.1590/s1806-37132012000500006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação quantitativa da intensidade da transpiração palmar e plantar em pacientes portadores de hiperidrose palmoplantar primária

Abstract: Objective: To compare individuals with and without hyperhidrosis in terms of the intensity of palmar and plantar sweating. Methods: We selected 50 patients clinically diagnosed with palmoplantar hyperhidrosis and 25 normal individuals as controls. We quantified sweating using a portable noninvasive electronic device that has relative humidity and temperature sensors to measure transepidermal water loss. All of the individuals had a body mass index of 20-25 kg/cm 2 . Subjects remained at rest for 20-30 min befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
6
0
2
Order By: Relevance
“…Nevertheless, it is a useful tool for clinical studies and comparison of pre- and postoperative results, in addition to allowing for documentation and recording. ( 2 , 5 , 7 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is a useful tool for clinical studies and comparison of pre- and postoperative results, in addition to allowing for documentation and recording. ( 2 , 5 , 7 )…”
Section: Discussionmentioning
confidence: 99%
“…Because it is easy to handle and portable, it can be used for pre- and postoperative comparison in the outpatient setting. ( 2 , 3 , 9 ) Steiner et al, compared the use of open-chamber and closed-chamber devices and concluded that, despite the advantages of each, the results were not comparable due to the different form of measurement. ( 10 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, assessing and quantifying hyperhidrosis clinically is not an easy task; therefore, I have read with great enthusiasm the study by Sakiyama et al describing a quantitative assessment of the intensity of palmar and plantar sweating in patients with primary palmoplantar hyperhidrosis. ( 1 ) …”
Section: To the Editormentioning
confidence: 99%
“…Por outro lado, avaliar e quantificar clinicamente a hiper-hidrose não é tarefa fácil; por isso, li com bastante entusiasmo o manuscrito de Sakiyama et al descrevendo uma avaliação quantitativa da intensidade da transpiração palmar e plantar em pacientes portadores de hiper-hidrose palmoplantar primária. ( 1 ) …”
Section: Ao Editorunclassified